Digital Transformation in Islamic Education: Integrating Kurt Lewin’s Change Model with Spiritual Values - Najiburrohman Najiburrohman; Raudlotul Hikmah; Samuel Femi Iliasu (Managere: Indonesian Journal of Educational Management, 2026)
This study aims to analyze the application of Kurt Lewin’s change management model to enhance digitalization in madrasah education while preserving Islamic principles. A qualitative case study design was employed to explore the contextual process of change. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model, which involves data condensation, reduction, presentation, and verification. The findings reveal that the Unfreezing stage involves the internalization of Islamic values within the digital consciousness of madrasah communities. The Changing stage reflects the integration of digital pedagogy and transformative leadership grounded in religious values. The Refreezing stage demonstrates the institutionalization of a digital-religious culture that defines the institution’s identity. These results indicate that combining Lewin’s change model with spiritual and cultural dimensions enhances both educational effectiveness and character development. The study implies that digital transformation in Islamic educational institutions can improve learning outcomes while reinforcing religious culture, offering a model for holistic digitalization in faith-based education.